Wheat aleurone layer: A site enriched with nutrients and bioactive molecules with potential nutritional opportunities for breeding. (July 2021) - Meziani, S.; Nadaud, I.; Tasleem-Tahir, A.; Nurit, E.; Benguella, R.; Branlard, G.
Abstract: Domesticated cereals (wheat, rice, corn, barley) contribute considerably to human nutrition providing energy, protein, micronutrients, vitamins, and antioxidants. In wheat, starch and protein accumulate in the endosperm whereas most of the phytonutrients are found in the aleurone layer (AL). The AL is the outermost layer of the endosperm and is removed with the bran in conventional milling. Many studies have been devoted to analyze this living tissue in cereal seeds, particularly in wheat. However, breeders still need to consider genetic and environmental factors that influence its properties and composition. The present survey focuses on recent advances achieved through proteomic and transcriptomic studies on the aleurone tissue. The origin of the AL in cereals, its mineral composition, antioxidants, nutrients and vitamins, the accumulation of globulins, and its major functions have been particularly highlighted. Studies dealing with the genetic factors involved in the variability of the AL components have also been emphasized. Improving the nutritional and health value of wheat for consumers is primordial. The present review proposes some approaches that could be developed through the AL traits breeding to improve the nutritional and health value of future wheat. Graphical abstract: Image 1 Highlights: The aleurone layer (AL) is rich in minerals, nutrients, vitamins and antioxidants. The A genome is predominantly expressed in AL of T. durum and T. aestivum species. Accumulation profiles of the globulin types (Glo-3, Glo-3B and Glo-3C) were shown. Major defense proteins accumulate independently between AL and endosperm. Numerous nutritional and healthy AL metabolites can be subjected to genetic breeding.